The role of journalistic style transformation in the development of news literacy - Mior Kamarulbaid, Afiqah; Wan Abas, Wan Anita; Omar, Siti Zobidah; Bidin, Rosmiza (Human Resource Management Academic Research Society, 2021)
This study aims to explore and understand the journalistic style prevalent on online news websites devoted to news literacy from the perspective of a media practitioner. The argument will first and mainly revolve around the journalistic approach that should be taken while reporting on digital news sites. Another critical job is determining the elements affecting the evolution of journalistic style in online news websites. The study's aims were accomplished by employing a semi-structured qualitative interview approach. Ten media experts were interviewed in-depth until the data set was saturated. According to the study's findings, journalists interact with their audiences in four unique journalistic approaches while teaching them about news items which has affected news literacy. Furthermore, the study's findings illustrate how journalistic style has evolved in the setting of online news websites. To fully appreciate how journalistic style has evolved in online news websites, media practitioners, educators, and journalism students must possess a working understanding of journalism history. This study aims to contribute to the body of knowledge by illustrating how the growth of journalistic style in online news websites has made new journalistic practices relevant.